2014
DOI: 10.1007/s11606-014-2811-3
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalist Career Decisions Among Internal Medicine Residents

Abstract: Hospital medicine is a reported career choice for an important proportion of graduating internal medicine residents. However, the majority of residents do not finalize this decision until their final year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…1,20 The U.S. decline may be due to numerous factors, including the dramatic growth in the number of specialists, health plans that enable direct access to specialty care for common conditions, specialist-oriented medical centers, and insufficient support of and payment for practices to comprehensively manage the expanding population of patients with comorbidities. 1,[21][22][23][24][25][26][27][28][29][30][31][32] In addition, patient-centered medical home (PCMH) 33,34 standards include other primary care features, such as accessibility and coordination, 35-38 but underemphasize comprehensiveness. 39,40 Some include a one-time health risk assessment and reminders about individual services for Bindividual conditions.^Although some PCMH recognition tools include care management plans that begin to address the notion of comprehensiveness, they seldom highlight the scope of services offered and the extent to which conditions and comorbidities are managed by the primary care practice.…”
Section: Why Measure Comprehensiveness Of Primary Care?mentioning
confidence: 99%
See 1 more Smart Citation
“…1,20 The U.S. decline may be due to numerous factors, including the dramatic growth in the number of specialists, health plans that enable direct access to specialty care for common conditions, specialist-oriented medical centers, and insufficient support of and payment for practices to comprehensively manage the expanding population of patients with comorbidities. 1,[21][22][23][24][25][26][27][28][29][30][31][32] In addition, patient-centered medical home (PCMH) 33,34 standards include other primary care features, such as accessibility and coordination, 35-38 but underemphasize comprehensiveness. 39,40 Some include a one-time health risk assessment and reminders about individual services for Bindividual conditions.^Although some PCMH recognition tools include care management plans that begin to address the notion of comprehensiveness, they seldom highlight the scope of services offered and the extent to which conditions and comorbidities are managed by the primary care practice.…”
Section: Why Measure Comprehensiveness Of Primary Care?mentioning
confidence: 99%
“…Practicing clinicians with primary care training do not necessarily provide comprehensive care. Despite receiving training in obstetrics, many family physicians do not provide obstetrical care, 42 and some internists trained in primary care competencies practice inpatient care exclusively 31,32 or in other narrow venues of care. 43,44 Lack of Professional Agreement on Respective Roles and Indications for Referral.…”
Section: General Challenges To Measuring Comprehensivenessmentioning
confidence: 99%
“…[4][5][6]23 As part of this effort, U.S. policymakers assumed that primary care and its workforce could be defined by the numbers of practicing physicians with generalist training (e.g., family medicine physicians, general internists, pediatricians and, in past decades, "general practitioners"), but changing roles now challenge this assumption. 24,25 Not all physicians trained as generalists practice primary care; many work as hospitalists and in urgent care or free-standing emergency departments, [26][27][28] on specialized care teams, and in consultative medicine. 29,30 Nurse practitioners and physicians assistants also contribute to primary care delivery, but many work instead in specialty care settings.…”
Section: What Is Primary Care?mentioning
confidence: 99%
“…7 Previous studies have shown that hospital medicine is an increasingly reported career choice for graduating residents in internal medicine (9.3% of graduating residents), through these studies suggest that many residents do not finalize this decision until their final year. 8 Looking at our results, a higher percentage of women select hospital medicine as a likely career choice. This is most likely related to a shorter length of training, as well as to perceived increased flexibility in scheduling.…”
Section: Discussionmentioning
confidence: 71%